Ethical Dilemmas and Their Impact on Accountability in Local Governments: A Study of the Greater Kigezi Sub-Region in Uganda - Katusiimeh, Mesharch Walto; Oketch, Chrisostom; Mucunguzi, Abel (East African Journal of Arts and Social Sciences, 2024)
This study examines the impact of ethical dilemmas on accountability in local governments within the Greater Kigezi sub-region of Uganda comprising of Kabale, Kanungu, Kisoro, Rubanda and Rukiga local governments and therefore, sufficient enough to represent and enable generalization of findings to other local governments in the country. Over the past few decades, public sector reforms have sought to enhance transparency, efficiency, and service delivery. Despite these efforts, Uganda continues to face challenges in maintaining strong accountability systems, particularly at the local government level. Ethical dilemmas—stemming from conflicts of interest, political pressure, resource constraints, and cultural norms—undermine accountability and transparency, leading to corruption and diminished public trust. The study investigates these dynamics by exploring how ethical challenges affect governance in local governments through the aid of questionnaires and interviews with stakeholders drawn from the local governments and opinion leaders who represent the voices of the grassroots. Focusing on the Greater Kigezi sub-region, the research highlights widespread governance issues such as nepotism, political interference, and weak institutional oversight. Findings reveal that ethical dilemmas hinder public sector performance by compromising decision-making and oversight processes. To address these challenges, the study suggests enhancing ethical training, strengthening oversight institutions, fostering civic engagement, and developing clearer policies on ethics and accountability. By implementing these policy reforms, stakeholders can create more transparent and accountable local governance systems that better serve community needs